Latitudinal dependence of short timescale fluctuations during intense geomagnetic storms: A permutation entropy approach. Issue 7 (30th July 2015) - De Michelis, Paola; Consolini, Giuseppe; Tozzi, Roberta
Abstract The present study is focused on the analysis of the latitudinal dependence of complexity degree of the short timescale geomagnetic field fluctuations during four intense geomagnetic storms occurring between 2000 and 2003. The aim is that of investigating the qualitative and quantitative changes in the dynamical properties of the magnetospheric system during magnetically disturbed periods. We analyze the short timescale fluctuations (<120 min) of the horizontal component of the Earth's magnetic field at nine different geomagnetic observatories from 49°N magnetic latitude (MLat) to 87°N MLat, by filtering the signal via empirical mode decomposition and successively by applying the permutation entropy analysis to the filtered time series. We show that some properties of the geomagnetic fluctuations during the selected periods are the result of dynamical changes in the magnetospheric system response to the solar wind changes and that these geomagnetic fluctuations display a complex character during the geomagnetic storm development. This evidence supports the idea that the geomagnetic storm nature may be the result of a cooperative and collective dynamics. We also find that the permutation entropy values change with latitude suggesting a latitudinal dependence of the complexity degree of the signals.